A synchrotron X-ray diffraction study of non-proportional strain-path effects. (1st February 2017) - Collins, D.M.; Erinosho, T.; Dunne, F.P.E.; Todd, R.I.; Connolley, T.; Mostafavi, M.; Kupfer, H.; Wilkinson, A.J.
Abstract: Common alloys used in sheet form can display a significant ductility benefit when they are subjected to certain multiaxial strain paths. This effect has been studied here for a polycrystalline ferritic steel using a combination of Nakajima bulge testing, X-ray diffraction during biaxial testing of cruciform samples and crystal plasticity finite element (CPFE) modelling. Greatest gains in strain to failure were found when subjecting sheets to uniaxial loading followed by balanced biaxial deformation, resulting in a total deformation close to plane-strain. A combined strain of approximately double that of proportional loading was achieved. The evolution of macrostrain, microstrain and texture during non-proportional loading were evaluated by in-situ high energy synchrotron diffraction. The results have demonstrated that the inhomogeneous strain accumulation from non-proportional deformation is strongly dependent on texture and the applied strain-ratio of the first deformation pass. Experimental diffraction evidence is supported by results produced by a novel method of CPFE-derived diffraction simulation. Using constitutive laws selected on the basis of good agreement with measured lattice strain development, the CPFE model demonstrated the capability to replicate ductility gains measured experimentally. Graphical abstract: Image 1